Introduction to participatory epidemiology and its application to highly pathogenic avian influenza participatory disease surveillance: A manual for participatory disease surveillance practitioners - Ameri, A.A.; Hendrickx, Saskia C.J.; Jones, B.; Mariner, Jeffrey C.; Mehta-Bhatt, Purvi; Pissang, C. (International Livestock Research Institute, 2009)
The purpose of this manual is to provide a reference for veterinarians and animal health workers during and after PDS training. The main focus of the manual is on HPAI PDS but the methods can be easily adapted and applied to address other livestock diseases.